The Effect of Environmental Costs and Green Investment on Sustainability Finance - Devina Nur Fitriani; Siti Kustinah (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study examines how environmental costs and green investment affect sustainability finance in coal mining subsector companies listed on the Indonesia Stock Exchange (IDX), especially during 2020 to 2024. This study uses a quantitative method with secondary data obtained from the company's annual report and sustainability report. The sampling technique used is purposive sampling so that 68 observation data that meet the research criteria are obtained. Hypothesis testing was carried out using t-test and F-test to analyze the partial and simultaneous influence of the study variables. The results of the partial test showed that environmental costs had a negative and significant effect on sustainability finance, while green investment had a positive and significant effect on sustainability finance. Meanwhile, the results of simultaneous testing show that environmental costs and green investment together have a significant effect on sustainability finance. The results of this study show the importance of effective environmental cost management and increasing green investment in supporting the company's financial sustainability. Further research is suggested to add moderation or mediation variables to clarify the factors that affect sustainability finance.